The osmoregulated metabolism of trehalose contributes to production of type 1 fimbriae and bladder colonization by extraintestinal Escherichia coli strain BEN2908 - Klemberg, Vivian Souza; Pavanelo, Daniel Brisotto; Houle, Sébastien; Dhakal, Sabin; Pokharel, Pravil; Iahnig-Jacques, Simone; Dozois, Charles M.; Horn, Fabiana (Frontiers in Cellular and Infection Microbiology, 2024)
In Escherichia coli, the disaccharide trehalose can be metabolized as a carbon source or be accumulated as an osmoprotectant under osmotic stress. In hypertonic environments, E. coli accumulates trehalose in the cell by synthesis from glucose mediated by the cytosolic enzymes OtsA and OtsB. Trehalose in the periplasm can be hydrolyzed into glucose by the periplasmic trehalase TreA. We have previously shown that a treA mutant of extraintestinal E. coli strain BEN2908 displayed increased resistance to osmotic stress by 0.6 M urea, and reduced production of type 1 fimbriae, reduced invasion of avian fibroblasts, and decreased bladder colonization in a murine model of urinary tract infection. Since loss of TreA likely results in higher periplasmic trehalose concentrations, we wondered if deletion of otsA and otsB genes, which would lead to decreased internal trehalose concentrations, would reduce resistance to stress by 0.6 M urea and promote type 1 fimbriae production. The BEN2908ΔotsBA mutant was sensitive to osmotic stress by urea, but displayed an even more pronounced reduction in production of type 1 fimbriae, with the consequent reduction in adhesion/invasion of avian fibroblasts and reduced bladder colonization in the murine urinary tract. The BEN2908ΔtreAotsBA mutant also showed a reduction in production of type 1 fimbriae, but in contrast to the ΔotsBA mutant, resisted better than the wild type in the presence of urea. We hypothesize that, in BEN2908, resistance to stress by urea would depend on the levels of periplasmic trehalose, but type 1 fimbriae production would be influenced by the levels of cytosolic trehalose.